Functional gastrointestinal disorders and nutritional status in junior high school students - Fatima Safira Alatas; Khansa Salsabila; Nadira -; Nasya Amalia; Gryselda Hanafi (Paediatrica Indonesiana, 2022)
Background The prevalence of functional gastrointestinal disorders (FGIDs) is increasing among students in Indonesia. More adolescents came to the clinic with symptoms of functional constipation (FC), irritable bowel syndrome (IBS), and functional dyspepsia (FD). Objective To analyze the relationship between the nutritional status, dietary pattern, and physical activity with the incidence of the FGIDs among Indonesian junior high school students. Methods A cross-sectional study, consisting of 292 students aged 11 to 14 years were recruited in March 2018. Questionnaires on the ROME Criteria for FGIDs, dietary patterns, and physical activity were distributed to the students’ parents and returned in 24 hours. Results The overall prevalence of FGIDs in this study was 26.4%. Among 292 junior high school students, 19.5% were diagnosed with FC, 6.2% with IBS, and 17.5% with FD. Overnourishment (overweight or obese) was found in 51.4% of the subjects. A significant association was found between FC and overnutrition (OR 2.27; 95%CI 1.21 to 4.28; P=0.011). Nutritional status did not affect the incidence of IBS nor FD. Rarely eating breakfast significantly increase the occurrence of FD (OR 4.80; 95%CI 1.61 to 13.25; P=0.004). No significant association between dietary patterns and physical activity with the prevalence of the other FGIDs. Conclusion Nutritional status does not significantly affect the prevalence of IBS and FD. Overnourishment is associated with increased occurrence of FC. Eating breakfast twice weekly or more may reduce the probability of FD. Lack of healthy dietary pattern and physical activity are not correlated with other FGIDs.